Operational cost of mechanized harvesting of first-crop coffee - Santinato, Felipe (2019)
The use of adapted harvesters for harvesting first-crop coffee requires a lower cost and exhibits a higher efficiency than manual harvesting. In view of this, the present study aimed to analyze the operational cost of mechanized harvesting of first-crop coffee. The experiment was conducted in a factorial scheme (2 × 3) + 1 and outlined in randomized blocks with five replications. There were seven treatments: two automotive harvesters (conventional and adapted) with times of operations for each harvester (1, 2 and 3 time operations) and manual harvesting. We tested these treatments in a young coffee crop planted in Catalão, GO, irrigated by Pivot, with 1.5 m of height. We measured the lost coffee, coffee harvest, remaining coffee before the operation to obtain efficient parameters and with the prices of the operations and the costs of the treatments. When operated once and three times, the adapted harvester required a lower transfer cost than the conventional harvester. Moreover, the adapted harvester showed no difference in cost between each operation. The cost reduction by mechanized harvesting varied from 23.96 to 59.9 %, depending on the frequency of the mechanized operations. In conclusion, it is efficient to harvest the young coffee with the adapted harvesters reducing the cost of coffee harvesting.